Gait analysis of teenagers and young adults diagnosed with autism and severe verbal communication disorders - Weiss, Michael J.; Moran, Matthew F.; Parker, Mary Elizabeth; Foley, John T. (Frontiers in Integrative Neuroscience, 2013)
Both movement differences and disorders are common within autism spectrum disorders (ASD). These differences have wide and heterogeneous variability among different ages and sub-groups all diagnosed with ASD. Gait was studied in a more homogeneously identified group of nine teenagers and young adults who scored as “severe” in both measures of verbal communication and overall rating of Autism on the Childhood Autism Rating Scales (CARS). The ASD individuals were compared to a group of typically developing university undergraduates of similar ages. All participants walked a distance of 6-meters across a GAITRite electronic walkway for six trials. The ASD and comparison groups differed widely on many spatiotemporal aspects of gait including: step and stride length, foot positioning, cadence, velocity, step time, gait cycle time, swing time, stance time, and single and double support time. Moreover, the two groups differed in the percentage of the total gait cycle in each of these phases. The qualitative rating of “Body Use” on the CARS also indicated severe levels of unusual body movement for all of the ASD participants. These findings demonstrate that older teens and young adults with “severe” forms of Verbal Communication Impairments and Autism differ widely in their gait from typically developing individuals. The differences found in the current investigation are far more pronounced compared to previous findings with younger and/or less severely involved individuals diagnosed with ASD as compared to typically developing controls. As such, these data may be a useful anchor-point in understanding the trajectory of development of gait specifically and motor functions generally.